Pengaruh Metode Small Group Discussion terhadap Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan di Kelas V Sekolah Dasar Negeri 105352 Pasar Miring - Gita Dama Yati; Nizmi Putri; Mastari Ramadhani (Medan Resource Center, 2025)
This study examines the effect of the Small Group Discussion method on students’ learning outcomes in Civic Education (PPKn) in Grade V at SD Negeri 105352 Pasar Miring. The research was motivated by the need to improve students’ conceptual understanding and active participation in Civic Education, which are often constrained by conventional, teacher-centered instruction. The study employed a quantitative experimental design with a pretest–posttest control group, involving 46 students divided into an experimental class taught using the Small Group Discussion method and a control class taught using conventional methods. Learning outcomes were measured using multiple-choice tests consisting of 15 pretest and 15 posttest items. The experimental class mean score increased from 63.77 (pretest) to 89.61 (posttest), while the control class rose modestly from 64.93 to 68.39. Independent t-test analysis confirmed a significant difference between both groups, and N-Gain analysis showed moderate effectiveness in the experimental class (65.73%) and low effectiveness in the control class (7.46%). These findings affirm that the Small Group Discussion method positively and effectively enhances students’ Civic Education learning outcomes.